Measuring seagrass photosynthesis: methods and applications - Silva, João (2018)
This review originates from a keynote lecture given at the recent 8th Group for Aquatic Productivity (GAP) workshop held in Eilat, Israel. Here we examine the most important methodologies for photosynthetic measurements in seagrasses and evaluate their applications, advantages and disadvantages, and also point out the most relevant results. The most commonly used methodologies are based on oxygen (O(2)) evolution and chlorophyll fluorescence measurements. O(2)-based methodologies allowed for the first approaches to evaluate seagrass productivity, whereas chlorophyll a fluorescence has more recently become the choice method for in situ experiments, particularly in evaluating photosynthetic responses to light and assessing stress responses. New methodologies have also emerged, such as O(2) optodes, underwater CO(2) flux measurements, geo-acoustic inversion and the eddy correlation technique. However, these new methods still need calibration and validation. Our analysis of the literature also reveals several significant gaps in relevant topics concerning seagrass photosynthesis, namely the complete absence of studies on deep-growing populations that photosynthesise under extreme low light conditions and the uncertainties about the true degree of seagrass carbon limitation, which limits our ability to predict responses to global changes.